The Social-Scientific Research: An Epistemological Discussion from Education - Omar Mejía-Pérez (Universidad Nacional, Costa Rica, 2011)
The epistemological debate of social-scientific research has been, for years, to compare the methods used, trying to determine which one is more valuable, according to its theoretical basis. Although more recent proposals use hybrid methods or more diverse epistemological approaches, duality has prevailed. Descriptive or explanatory; phenomenology or positivist; classical or emergent; research paradigms are our way to access to the reality studied and obtain principles and answers. This defines the methods. Even when, it is possible to group and categorize these methods as quantitative and qualitative, the epistemological framework established by the structures of any methodology will allow approaching a phenomenon better than other, although, this does not necessarily make it definitely more valuable. Both quantitative and qualitative methods, in education, have helped to address phenomena, which has produced favorable results to benefit the education activity. This trial, which is the result of a literature review and a career in research and education, aims at clarifying the complex initial overview of new educational researchers, instead of reviewing an epistemological position.